Researching the identity of a city – The case of Osijek, Croatia - Kamenov, Željka (Array, 2008)
Citizens of a certain city can, for different reasons, be dissatisfied with the image of their city and be interested in re-positioning people's perception of it to a more favorable one. City branding is a strategic process for developing a long-term vision for a place that influences and shapes positive perceptions. Developing a strategy for city branding first requires an in-depth knowledge of the city identity itself. What are the key characteristics of the city? Which of its symbols are recognized? What are the people like? What is it like to live in it? What are its potentials? It’ s advantages and disadvantages? What should the city be like in the future? This paper explains the methodological steps used in researching an identity of a city. The main goal of this research was to assess the identity of the city of Osijek, Croatia. An elaborate research strategy combined both qualitative and quantitative methodology. In-depth interviews with city opinion makers and focus groups with representatives of different areas relevant for the city were conducted. Additionally, 1097 people participated in a detailed survey. These steps enabled us to find out how do people involved in city policy making see Osijek, what citizens of Osijek think about the town they live in, and finally, how citizens from other cities in Croatia perceive it.